Review on Linear and Non-Linear Programming: Optimization of Product Combinations for Maximum Return in a Paint Organization (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The motivation behind the study is to feature the adequacy of linear programming in the determination of the optimal combination of different items that an organization produces to augment contribution. For this reason, information for the month of July 2016 of a paint organization in Pakistan has been acquired for one of the primary items Plastic Emulsion that is delivered in three unique sizes (quarter, gallon and drum). The simplex strategy is utilized to decide the optimal blend of these sizes to be created to boost contribution. The outcomes show that the organization can acquire maximum contribution by only contributing its assets (crude material) in the production of a gallon and creating 444 units of it along these lines producing contribution Rs. 162038. This study will perceive this organization and likewise to the next assembling organizations, especially in Pakistan, with the adequacy of linear programming for settling on decisions about the optimal combinations of items to be delivered to get the maximum return.